Survey on Patients\' Satisfaction with the Services Provided at Pharmacies in the City of Kashan - Hamidreza Banafsheh; Hamidreza Gilasi; Amir Ghaderi (Journal of Advanced Biomedical Sciences, 2019)
Background & Objective: Patients’ satisfaction is a key factor in the evaluation of health system’s quality in developed countries. The purpose of the presnt study was to investigate Patients’ satisfaction with services provided at pharmacies in the city of Kashan and related elements. Materials & Methods: In a cross- sectional study, 440 patients who referred to pharmacies in the city of Kashan were surveyed randomly. The questionnaire was composed of 44 items and focused on four dimensions: patients’ expectations from the pharmasict, pharmacist’s communication skills, consultations offered by the pharmacist, and the location and physical environment of the pharmacy. In order to analyze the data of this study, SPSS software version 20, and parametric and ANOVA tests were used. Results: Patients’ highest expectations were courteous behavior from the pharmacist and the personnel (92/7%), low wating time (92%), explanation for medication indications (85%), and explanation on how to use the medications (82/5%). Patients’ satisfaction elements with the highest score were cordial and pleasant attitude of the pharmacist (78.9%), labeling the medications by the pharmacist (78%) and the illumination inside the drugstores facility (93%). Conclusion: The city of Kashan has variable levels of satisfaction with the quality of pharmacy services. To increase levels of satisfaction, it is necessary to provide appropriate training in pharmacies and quality of services promted in all domains.